1991
DOI: 10.1002/iroh.19910760407
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Chlorophyll‐containing Picoplankton Populations of Ten Lakes in Northern England

Abstract: Key features of photosynthetic picoplankton populations were compared during 1988 in ten lakes in northem England ranging from oligotrophic to slightly eutrophic; two of the three eutrophic lakes were shallow and lacked a thermocline. Measurements were made at 0.5 m depth of temperature, total chlorophyll a, chlorophyll-containing picoplankton cell density, mean picoplankton Celt volume and percentage of phycoerythrin-rich cells in the total picoplankton population. All lakes showed maxima for total chlorophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
4
20
1
Order By: Relevance
“…The participation of APP as a component of the total phytoplankton biomass in the Warta was not significant. This confirms the observation of Hawley and Whitton (1991b), that relative contribution of APP to total phytoplankton biomass is the lowest when the trophic state is high. Autotrophic picoplankton is observed in waters of different trophic state, but studies show the sensitivity of APP to eutrophication, and also to water contamination, especially with heavy metals (Severn et al 1989;Weisse 1991;Weisse and Mindl 2002).…”
Section: Discussionsupporting
confidence: 91%
“…The participation of APP as a component of the total phytoplankton biomass in the Warta was not significant. This confirms the observation of Hawley and Whitton (1991b), that relative contribution of APP to total phytoplankton biomass is the lowest when the trophic state is high. Autotrophic picoplankton is observed in waters of different trophic state, but studies show the sensitivity of APP to eutrophication, and also to water contamination, especially with heavy metals (Severn et al 1989;Weisse 1991;Weisse and Mindl 2002).…”
Section: Discussionsupporting
confidence: 91%
“…While some studies of temperate lakes have shown two peaks of picocyanobacteria abundance, one in spring and one in late summer (Weisse, 1993;, other lakes lack a spring peak, with only a summer or autumn population maximum (Pick & Agbeti, 1991;Maeda et al, 1992;Hawley & Whitton, 1991). Our data suggest that CWP lakes 9 and 124 exhibit one peak, in summer, for all clades with the exception of clade I.…”
mentioning
confidence: 40%
“…Large spring peaks were found in Lake Constance (WEISSE, 1993) and Lake Maggiore (STOCKNER et al, 2000) and are also common in eutrophic and hypertrophic lakes (SIME- NGANDO, 1995;VÖRÖS et al, 1991;JASSER, 1997), but not in warm-monomictic lakes (STOCKNER and SHORTREED, 1991;MALINSKY-RUSHANSKY et al, 1995). The seasonal patterns found in seven Danish lakes (SØNDERGAARD, 1991), several Canadian lakes (PICK and AGBETI, 1991), Lake Biwa, Japan (MAEDA et al, 1992) and in the northern English lakes (HAWLEY and WHITTON, 1991) all lack the spring peak, there being only a summer or autumn maximum. The bimodal pattern of APP abundance in PG was similar to that reported by JASSER (1997) in the shallow, dystrophic lake Flosek (Poland).…”
Section: Picoplankton Seasonal Dynamics and Controlling Factors In Wementioning
confidence: 88%